Unsur Balaghah dalam Surah al-Qari’ah (Telaah Kitab Safwah al-Tafasir) - Muhammad Addien Nastiar (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2023)
The Mufassirins have done many interpretations of the Quran, with the various methods they use. One of the sciences that supports the interpretation of the Qur'an is the science of Balaghah. Balaghah serves to explain the meaning contained in the Arabic language used by the Quran. Balaghah also plays a role in the beauty contained in a verse. The book of Shafwatut Tafasir was written by Sheikh Ali Ash-Shabuni, one of the supporting aspects in its interpretation is Balaghah. This article will discuss the analysis of the balaghah of surah al-Qari'ah in the book of Shafwatut Tafasir. Surah al-Qari'ah generally discusses the Day of Judgment. This article aims to discuss the depth of meaning and beauty of language in the surah al-Qari'ah by referring to the book of Shafwatut Tafasir. And with this article, it is hoped that Muslims will become more acquainted with the science of interpretation and understand the Quran well by referring to the interpretation of the Mufasirins. So, that Muslims avoid misunderstandings and can use the Quran as a guide for life and can achieve happiness in this world and the hereafter.